2014
DOI: 10.1021/ar500051r
|View full text |Cite
|
Sign up to set email alerts
|

DNA Nanostructures Interacting with Lipid Bilayer Membranes

Abstract: CONSPECTUS: DNA has been previously shown to be useful as a material for the fabrication of static nanoscale objects, and also for the realization of dynamic molecular devices and machines. In many cases, nucleic acid assemblies directly mimic biological structures, for example, cytoskeletal filaments, enzyme scaffolds, or molecular motors, and many of the applications envisioned for such structures involve the study or imitation of biological processes, and even the interaction with living cells and organisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
180
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(183 citation statements)
references
References 60 publications
3
180
0
Order By: Relevance
“…The studies described in this manuscript complement the research of various scientific groups whose work is focused on the formation of complex nanoarchitectures [33ā€“34], the interaction of such nanostructures with lipid membranes [35ā€“38], as well as the optimization of the in vivo delivery of lipophilic siRNA [10ā€“12] (e.g., by DNA trafficking [7]).…”
Section: Resultsmentioning
confidence: 99%
“…The studies described in this manuscript complement the research of various scientific groups whose work is focused on the formation of complex nanoarchitectures [33ā€“34], the interaction of such nanostructures with lipid membranes [35ā€“38], as well as the optimization of the in vivo delivery of lipophilic siRNA [10ā€“12] (e.g., by DNA trafficking [7]).…”
Section: Resultsmentioning
confidence: 99%
“…45 They further found that at suitable salt concentrations, charged polymers (polyethyleneamine) are adsorbed onto the surface of DMPC vesicles. Similarly, Langecker and co-workers 46 specifically studied DNAāˆ’lipid interactions and how DNA nanostructures can either remain mobile on membranes or can be embedded within lipid bilayers. Interestingly, Bo and coworkers 47 also found via fluorescence and calorimetry methods that the local phase state of phospholipid bilayers can be switched by binding of charged nanoparticles such that they alter the tilt angle of the phosphocholine.…”
mentioning
confidence: 99%
“…The importance of the topic was emphasized in a recent review (Langecker et al 2014). For this, a synthetic system currently developed for transfer of therapeutic nucleic acids into target cells using a synthetic DNA supramolecular assembly is presented.…”
Section: Resultsmentioning
confidence: 99%